PENGARUH PENGUNGKAPAN LINGKUNGAN PERUSAHAAN DAN BOARD CONNECTION TERHADAP MANAJEMEN LABA RIIL - Nathanael Antoro Budi Pangestu (2022)
This study aims to examine the influence of corporate environmental disclosure which consists of 5 aspects such as environmental policy, environmental pollution, environmental energy, environmental financial, environmental other, and board connection on real earnings management. The data used in this study is secondary data using annual reports and sustainability reports of companies in the non-financial sector on the Indonesia Stock Exchange during the period 2018 to 2020 with a total sample used of as many as 93 companies. The analysis method used is panel data regression analysis using STATA 14. The test results show that corporate environmental disclosure (environmental policy, environmental pollution, environmental energy ,environmental financial, environmental other) and board connection have no significant effect on real earnings management. This research has implications, namely as a basis for research on real earnings management that will be carried out further and this research provides awareness to management, regulators, stockholder and creditors about real earnings management problems in companies.